Inserção profissional e pesquisa-formação: uma experiência formativa com professoras do Atendimento Educacional Especializado (AEE) em sala de recursos multifuncionais da Rede Municipal de Ensino de Santo André - Conceição, Carla Patrícia Ferreira da (2024)
This qualitative research aims to analyze how the professional insertion of Specialized Educational Service teachers in Multifunctional Resource Rooms occurs based on researchcontinuing education, through collaborative partnership contributions among beginning, newly qualified and experienced teachers and the researcher. It intends to collectively identify the continuing education needs of the Specialized Educational Service teaches in the Multifunctional Resource Rooms for the organization and development of continuing education meetings; discuss if the continuing education proposal enabled beginning, newly qualified and experienced teachers to reflect on their own work; and understand the contributions of this research-continuing education focused on a collaborative work among these teachers in their continuing education process. The literature review encompasses an overview of national public policies in special education from the perspective of inclusive education and discusses the Specialized Educational Service teacher continuing education policies. It presents studies that discuss the teaching professional insertion process, professional support actions for teachers at the beginning of their career and professional induction. Thirty-six teachers participated in this research, which is based on the theoretical and methodological principles of research-continuing education. Document analysis, participant characterization forms, continuing education meetings, and oral/written narratives were used to produce data. The collected data were analyzed using the prose analysis method, which enabled to formulate three axes of analysis: teachers’ professional insertion and continuing education needs; researchcontinuing education and process of reflection on one’s own work; and contributions of this research-continuing education in collaborative actions among beginning, newly qualified and experienced teachers in the continuing education process. The main findings show that teachers experienced professional insertion facing numerous challenges, such as lack of experience, didactic-pedagogical repertoire, work conditions, and isolation in some schools, which heightens these challenges. The actions carried out allowed participants to learn about individual and collective challenges, anxieties, and knowledge, which led to the construction and development of meetings with horizontal relationships. The strategies applied favored the recovery of the historical process of life and the professional development of each participant, biographical reflexivity, anchored in experience and memory in a temporality, and learning about themselves and others from the narrative of their experience. The actions developed through research-continuing education enabled both experienced teachers to reflect on their own work and beginning/ newly qualified teachers to professional socialization, which proved to be an element of distinction in the participants’ professional insertion process